Sharing Experience dan Resiliensi: Studi atas Facebook Group Orang Tua Anak Cerebral Palsy - Rovasita, Safrina (PLD UIN Sunan Kalijaga, 2017)
Cerebral Palsy is a brain disorder that affects a motor area. Parents who have a child with Cerebral palsy are usually sorrowful. They feel hopeless and inferior because of their inability to manage their stress, and their resilience is poor. The level of stress management for each parent is different. For that reason, parents join an online group created on the Facebook online. Among the typical objective of joining such groups is to share their experience of having children with cerebral palsy. Is there any positive effect of this sharing experience toward their resilience? This study used a mixed method to answer this question. The quantitative data are collected by using questionnaire with a scale of CD-RiSC resilience and scale of sharing experience Response. This quantitative data is then elaborated by interviewing the participants by using purposive sampling technique. The research found that the Facebook group indeed helps the parents in improving their resilience. It is achieved by additional information and knowledge they learn from the group.[Orang tua yang mendapati anaknya terfonis sebagai anak Cerebral Palsy mengalami kedukaan mendalam yang mengakibatkan ketidakpercayaan diri, dan putus asa. Hal itu diakibatkan ketahanan terhadap stres (resiliensi) rendah, oleh karena itu orang tua mengikuti sharing experiences penyandang Cerebral Palsy melalui Facebook Group orang tua anak Cerebral Palsy. Penelitian ini bertujuan menjawab pertanyaan adakah pengaruh sharing experiences penyandang Cerebral Palsy terhadap resiliensi orang tua anak Cerebral Palsy yang terhimpun dalam Facebook Group Orang Tua Anak Cerebral Palsy. Penelitian menggunakan methode kombinasi antara kuantitatif dan kualitatif. Penelitian menemukan bahwa Facebook Group berpengaruh pada peningkatan resiliensi orang tua anak cerebal palcy karena mereka mendapatkan pengetahuan dan informasi tambahan dari forum itu.]